Snake bite prevalence & outcome of poisonous snake bite in Patuakhali Medical College Hospital, Patuakhali (The Planet, 2022)
Background: Snakebite envenoming is increasingly recognized as a major, deadly tropical disease of public health importance. Early antivenom treatment of snakebites might reduce the severity of thrombosis and systemic bleeding, the incidence of acute renal failure, and the length of the recovery time. Objective: To find out the prevalence and outcome of poisonous snake bite. Methodology: The present descriptive observational study was carried out in medicine wards of Department of medicine, Patuakhali Medical College Hospital during January’ 2016 to December’ 2020. A total of 580 cases of snake bite were admitted in medicine wards during the study period. Among them 116 cases were poisonous Snake bites. In this study we included 116 poisonous Snake bite cases. Results: Prevalence of poisonous Snake bite cases was 116(20%). Majority patients came from rural area 95(81.9%) and 21(18.1%) came from urban area. Majority 80(69.0%) patients had neurotoxicity, 51(44.0%) had local pain, 49(42.2%) had cellulitis, 20(17.2%) had gangrene, 10(8.6%) had hematotoxicity, 10(8.6%) had acute renal failure, 9(7.8%) had coagulopathy, 9(7.8%) had oedema and 8(6.9%) had severe headache. Out of 116 patients, anti-venom given 110(94.8%), death 20(17.2%), broad death 4(3.4%), snake identification 10(8.6%), out of which Kobra was 8(6.9%) & Russel’s Viper 2(1.7%). Adverse effect (Anaphylactic reaction) due to venom 10(8.6%), adrenalin given 18(15.5%), endotracheal intubation & ICU transfer 2(1.7%) and referred was 3(2.6%) patients. Conclusion: Prevalence of poisonous Snake bite cases was 20%, common complications due to snake bite were local pain, cellulitis, coagulopathy, hematotoxicity, oedema, acute renal failure, neurotoxicity and ulcer of limb.
Keywords: Snake bite; complications; outcome; management